Studying on Learning Satisfaction in Teaching Keyboard Courses With Problem-Based Learning Teaching Mode - Ko, Chia-hui (Frontiers in Psychology, 2022)
Lifelong learning has become a trend in an increasingly aging society. Adult musical instrument learning is becoming more and more common, especially in keyboard music learning. With the learning characteristics of adults, such as self-directed learning, courses that are preferred in application and practice, this research explores the Problem-Based Learning (PBL) teaching method employed in adult keyboard music learning courses. Applying the PBL teaching method as the theoretical basis, this study established a research model and investigated the correlation of learning satisfaction with influencing factors such as teaching effectiveness, self-efficacy, and teamwork and verified teaching effectiveness, self-efficacy, and teamwork relationships. Research data has been collected from the keyboard music students of the two classes of the Arts & Culture Department in Open University of Kaohsiung. Data analysis was conducted in three stages: descriptive statistics, measurement model verification, and structural equation model. The results of the study found that teaching effectiveness has a significant impact on learning satisfaction. Teamwork also has a significant positive impact on learning satisfaction. However, the self-efficacy dimension has little effect on learning satisfaction. Finally, through the research results, the higher the adult learners’ perception of teaching effectiveness, the higher their learning satisfaction. The better the adult learners’ employ of teamwork, the higher their learning satisfaction. The results of the study found that teaching effectiveness and teamwork both have significant impacts on learning satisfaction. However, the self-efficacy dimension has little effect on learning satisfaction. This study verified the effectiveness of the PBL teaching model in the adult keyboard music curriculum. Teamwork is a key factor for its success, and the teaching effective-ness of teachers plays an indispensable role in teamwork. Due to the COVID-19 pandemic, the presentations of the final results in the courses were transferred from entities to online presentations. The student-led presentations went smoothly and the results were quite remarkable, which became a reference for the implementation of other courses for adults in the future.